تقنيين مقياس ميداس للذكاءات المتعددة لطلاب الصف الحادي عشر في محافظة شمالي الباطنة بسلطنة عمان: Standardization of MIDAS with Grade Eleven Omani Students in the Governate of North Albatinah - ALmazruii, Abdul Aziz Abdullah Mohammed; Ibrahim, Ali Mohammed; Almehrizi, Rashid Saif; Alzubaidi, Abdul Qawi Salem (IIUM Journal of Educational Studies, 2020)
The purpose of this study was to examine the psychometric properties of Shearer’s (1996) Multiple Intelligence Developmental Assessment Scale (MIDAS) used with a sample of Grade 11 Omani students. The sample consisted of 700 Grade 11 students (321 males and 379 females) from the Governorate of North Albatinah in the Sultanate of Oman. The study also administered the Raven progressive matrices test and the verbal intelligence test to two different samples of 120 and 103 students, respectively, for concurrent validity. The data analysis was conducted using SPSS and LISREL8.14. The results showed that MIDAS has acceptable construct and concurrent validity for both tests. Also, the results of a confirmatory factor analysis (CFA) showed acceptable goodness of fit indices for MIDAS. Similarly, both the internal consistency and test-retest reliability of the scale showed satisfactory results. Finally, the percentile ranks for MIDAS scores were computed as norm scores for the scale. In conclusion, the study confirms the possibility of using the MIDAS test for career guidance purposes. It also provides indicators to identify the multiple intelligence levels of students with the aim of enhancing their intellectual capability using appropriate instructional methods and activities.